Risk Analysis and Sustainability of Sharia Insurance in Facing the Challenges of the Digital Era - Rahmadhani, Layla; Ramadhan, Muhammad; Rahmani, Nur Ahmadi Bi (PT Mattawang Mediatama Solution, 2024)
Digitalization of Islamic finance leverages technology to enable financial transactions anytime and anywhere, removing specific time constraints. This research explores the challenges, opportunities, and risks associated with digitalization in the sharia insurance sector. Utilizing qualitative methods with a descriptive approach, the study reveals that challenges include: a) Upholding sharia principles in technology adoption, b) Ensuring security and compliance, c) Addressing bias in big data and AI, d) Forming strategic partnerships with fintech, and e) Investing in sustainable projects. Opportunities for digitalization in sharia insurance encompass: a) Easier customer reach, b) Enhanced customer education and facilities, c) Streamlined transactions and SOP completion, d) Broader introduction of sharia insurance, e) More effective marketing, and f) Collaborative efforts. Risks associated with digitalization can be mitigated by: a) Providing robust customer protection, b) Enhancing trust and security, and c) Reinforcing justice and sustainability. This research aims to provide a comprehensive understanding of these aspects to better guide the implementation of digital technologies in the sharia insurance sector.